Jean Waldman collection of Civil War papers - Waldman, Jean.
Correspondence, reports, paroles and passes, map, and other papers primarily regarding the Confederate campaign in southwestern Virginia. Correspondence relates chiefly to the Union Army's intelligence network and cryptography and to requests for baggage and ambulance transportation for homeward bound troops. Includes a print and manuscript copy of Robert E. Lee's General Order No. 9 announcing the surrender of the Army of Northern Virginia and a manuscript map depicting the area around Saltville, Va. Correspondents include Nathaniel Folsom, A.P. Hill, Robert E. Lee, Dabney Herndon Maury, Winfield Scott, James A. Seddon, William Farrar Smith, and John H. Winder. Also includes an 1817 carriage tax certificate.
Collection material in English.
Keywords: Folsom, Nathaniel, -- 1726-1790 -- Correspondence; Hill, A. P. -- Correspondence; Lee, Robert E. -- 1807-1870.; Lee, Robert E. -- 1807-1870 -- Correspondence; Maury, Dabney Herndon, -- 1822-1900 -- Correspondence; Scott, Winfield, -- 1786-1866 -- Correspondence; Seddon, James A. -- 1815-1880 -- Correspondence; Smith, William Farrar, -- 1824-1903 -- Correspondence; Winder, John H. -- 1800-1865 -- Correspondence; Confederate States of America. -- Army; Confederate States of America. -- Army of Northern Virginia; United States. -- Army -- History -- Civil War, 1861-1865.; Confederate States of America -- History; Saltville (Va.) -- Maps; Virginia -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Maps; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Cryptography; United States -- History -- Civil War, 1861-1865 -- Military intelligence; United States -- History -- Civil War, 1861-1865 -- Peace; United States -- History -- Civil War, 1861-1865 -- Transportation